The Analysis Of Educational Thought According To Ibn Sina And Its Relevance In Islamic Education In The Modern Era - yasmansyah; Lainah; Wedra Aprison (International Journal Of Humanities Education and Social Sciences (IJHESS), 2021)
This study aims to analyze the educational thought according to Ibn Sina and its relevance in Islamic Education in the modern era. The method used in this study uses a library method or approach (library research). Data obtained through literature study. The results showededucational thought of Ibn Sina are the concept of educational goals, the concept of learning methods, the concept of the educational curriculum. There were seven educational methods offered by Ibn Sina, namely: (1) Talqin, this method is used in reading the Koran by hearing the reading of the Koran to students in stages, (2) Demonstration, method this is used in writing lessons, (3) modeling and habituation, this method is used in learning morals, (4) Discussion, this method is carried out by the teacher describing a problem in a lesson to be solved together by students, (5) Apprenticeship, this method is used so that students can combine theory and practice, where students are asked to practice the theory they have obtained, (6) Assignment, this method is done by the teacher preparing and giving modules to students to learn, and (7) targhib and tarhib, this method in modern education is known as reward (reward) and punishment (punishment). The sources of Islam and Islamic education are the same, namely the most important, the Koran and the Sunnah of the Prophet. Therefore, Ibn Sina's conception of education is still very relevant when applied today